Linking Workplace Ostracism to Job Performance : A Conceptual Framework Considering the â€˜New Normalâ€™ Situation - Giri, Arunangshu; Chatterjee, Satakshi; Salo, Jari (Prabandhan: Indian Journal of Management, 2023)
Workplace ostracism is a ubiquitous phenomenon that is present across the majority of organizations. However, it is often ignored, which results in dire consequences for the employees as well as the organizations. Workplace ostracism directly affects the job performance of employees. Also, after the emergence of the COVID-19 pandemic, organizations are still adjusting to the â€œnew normal.â€ As this situation has never been foreseen before, at this point in time, workplace ostracism is becoming an emerging issue across organizations today. This short communication aimed to delve deeper into the phenomenon of workplace ostracism, find out the relationship between workplace ostracism and the employeesâ€™ job performance, and develop a conceptual model. This conceptual model has been developed with the help of extensive current literature review. The findings revealed that workplace ostracism had an impact on the employeesâ€™ personal and professional facets, leading to the variation of employee performance. Also, moderating variables like external support, culture, and religiousness remarkably impacted the relationship between workplace ostracism and different facets. As a result, this study can be used as a reference for HR managers to develop strategies to impede the growth of workplace ostracism in their respective organizations.